Análisis crítico de la racionalidad patriarcal en Male and Female (1949) de Margaret Mead - López Báez, Margarita (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
This research is a critical analysis of the work Male and Female (1949) by the renowned American anthropologist Margaret Mead, a key figure in feminist anthropology and gender studies. This analysis is grounded in philosophical feminism and the analytical categories of patriarchal rationality, and some others that are interwoven in it, such as binarism, gender and compulsory heterosexuality. I construct the analysis by considering the genre of the work from the social perspective, a review from social cognition and finally integrate this into the critical analysis itself. The analysis is focused on the macrostructure, the local meanings and the implicit meanings for being the most suitable to the ideological expression. The ideological bias in the work is a complex phenomenon to elucidate, since the author problematizes perhaps as much as she reproduces patriarchal rationality.

La presente investigación es un análisis crítico de la obra Male and Female (1949), de la reconocida antropóloga estadounidense Margaret Mead, figura clave en la antropología feminista y en los estudios de género. Este análisis está fundamentado principalmente en el feminismo filosófico y en las categorías analíticas de racionalidad patriarcal, y algunas otras que se entretejen en esta, como binarismo, género y heterosexualidad obligatoria. Construyo el análisis considerando las características discursivas de la obra desde la perspectiva social, una revisión desde la cognición social y finalmente integro esto en el análisis crítico propiamente. El análisis está enfocado en la macroestructura, los significados locales y los significados implícitos por ser elementos en los cuales se puede identificar la expresión ideológica. El sesgo ideológico en la obra es un fenómeno complejo de dilucidar, ya que la autora problematiza quizá tanto como reproduce la racionalidad patriarcal.
Facultad de Letras. Maestría en Estudios del Discurso
Keywords: info:eu-repo/classification/cti/4; FL-M-2024-0499; Racionalidad patriarcal; Binarismo; Heterosexualidad obligatoria; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18657